تحليل واقع خدمات الدفاع المدني في محافظة عجلون - الأردن باستخدام نظم المعلومات الجغرافية - الخاروف، ريم عدنان واصف; المومني، منار; هزايمة، خالد محمد أمين Hazaime, Khalid (جامعة آل البيت - عمادة البحث العلمي, 2018)
This study aimed at evaluating the current situation of civil defense services including emergency and fire fighting in Ajloun governorate in Jordan by defining the non-served area, and best routes to reach the incident locations. Here, the analytical approach was used to measure the effectiveness and performance of civil defense centers to reach those locations based on time and distance as the evaluation criteria. Thus, three and five minute thresholds were used to define the service areas of emergency and firefighting services, respectively. Several pre-processing steps were made including street network topology evaluation, producing land use and slope maps based on Landsat-8 and ASTER-GDEM remote sensing imagery. These images were used to define the estimated travel time from civil defense center to incident locations. After that, a network analysis within geographical information systems (GIS) environment was performed for the evaluation process. Results showed that several settlements were not served by civil defense services according to the pre-defined criteria (i.e., three and five minutes) for emergency and firefighting services, respectively. Also, it showed the capability of GISto define the best routes to reach the incident location within the shortest distance or fastest speed.
هدفت الدراسة إلى تقييم على واقع خدمات الدفاع المدني وخاصة الاسعاف والاطفاء في محافظة عجلون من خلال تحديد المناطق غير المخدومة بهذه الخدمات بالإضافة إلى تحديد الطرق الأنسب التي ستسلكها آليات الدفاع المدني للوصول إلى مواقع الحوادث. وقد اعتمدت الدراسة على المنهج التحليلي لقياس أداء وفاعلية مراكز الدفاع المدني في الوصول إلى المواقع التي تحتاج إلى خدماتها وفقا لمعايير محددة لهذا الغرض (المسافة، والزمن) حيث تم اعتماد معيار الثلاث دقائق لتحديد المناطق المغطاة بخدمات الإسعاف، ومقدار الخمس دقائق لتحديد المناطق المغطاة بخدمات الإطفاء. وقد تمت عملية التحليل في بيئة نظم المعلومات الجغرافية بالاعتماد على تحليل الشبكات (Network Analysis) بعد أن تمت عمليات تحضيرية لشبكة الطرق كتعديل الأخطاء المكانية الطبولوجبة Topological Errors وإنتاج خريطتي استعمالات الأرض والانحدار بالاعتماد على مرئيات الاستشعار عن بعد لاندسات Landsat-8 في العام 2015م، والمرئية Aster-GDEM على التوالي. وقد تم الاستفادة من هاتين الخريطتين في ضبط حدود السرعة على شبكة الطرق بالإضافة إلى نوع وحالة الطريق. وتوصلت الدراسة إلى عدد من النتائج أهمها: وجود عدد من التجمعات السكانية في محافظة عجلون غير مغطاة بخدمات الإسعاف والإطفاء بحسب معياري الثلاث والخمس دقائق على التوالي. بالإضافة إلى قدرة نظام المعلومات الجغرافية على تحديد المسار الأنسب للوصول إلى مناطق الحوادث بأقصر طريق أو أقل فترة زمنية.
Keywords: جغرافية الخدمات -- الدفاع المدني -- تحليل الشبكات -- شبكة الطرق -- نظم المعلومات الجغرافية -- محافظة عجلون -- الأردن